FORMATION OF SPINEL FORM HYDROTALCITE-LIKE MINERALS AND DESTRUCTION OF CHROMITE IMPLANTED BY INORGANIC SALTS - Moroz T.; Razvorotneva L.; Grigorieva T.; Mazurov M.; Arkhipenko D.; Prugov V. (My University, 2001)
Thermal decomposition of natural hydrotalcites HT and the role of hydrotalcite-like materials in the destruction of solid Ž. with a spinel-type structure, after grinding with solid phase Na CO additives, are investigated by means of infrared IR 2 3 Ž. spectroscopy and X-ray powder diffraction XRD methods. The thermal treatment of hydrotalcite results in intermediates with contents and structures, which essentially depends on impurities in natural samples, conditions of treatment, as well as the environment. In this study, chromite implanted by inorganic salts is used to illustrate the influence of the mechanical Ž activation of the process to convert spinel to hydrotalcite-like structures. It has been found that the small concentration 4. wt.% of solid-phase admixture, implanted in the layers near the surface, is favorable for enhancement of the structural changes.
Keywords: hydrotalcite; spinel; destruction; infrared spectra